La santé animale 2. Principales maladies - Hunter, Archie (éditions Quae, 2006)
"This second volume La santé animale covers the main livestock diseases in detail: infectious and parasitic diseases, vector-borne diseases, and diseases linked to the environment and to rearing conditions. Each disease is described - symptoms, causes, mode of transmission and spread-, along with the relevant treatments and preventive measures. Intended for veterinary technicians and agricultural counsellors, this technical work provides clear, essential information for anyone working with or in charge of treating animals in the tropics and subtropics. It can also be used for teaching purposes, in the higher education sector."